2020
DOI: 10.14505//jemt.v11.3(43).11
|View full text |Cite
|
Sign up to set email alerts
|

The Conceptual Framework for Water Accounting in Sustainability of Peatland Ecosystems. An Islamic Perspective

Abstract: Water accounting is a new topic that discusses the impact of environmental changes where the existence of water as one of the most vital natural resources is becoming increasingly scarce. The conceptual framework of water accounting should include the element or value of Ihsan. That is, it is expected that users will be able to implement the Ihsan value in water accounting. The environment is an ecosystem created entirely by God for human life. The value of Ihsan in the conceptual framework of water accounting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…This method serves to drain the land so that it can be planted. Creating drainage or canals to protect water in peatlands without draining it into rivers [11]. In long-term use, this method harms the peat ecosystem if the canals are drained into rivers.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…This method serves to drain the land so that it can be planted. Creating drainage or canals to protect water in peatlands without draining it into rivers [11]. In long-term use, this method harms the peat ecosystem if the canals are drained into rivers.…”
Section: Findings and Discussionmentioning
confidence: 99%
“…In previous another study, Miettinen & Liew (2010) also identified the main cause of fires on peatlands in Sumatra and Kalimantan, especially land clearing for industrial plantation forests (HTI). Several other studies have also identified that in addition to natural factors, the role of humans individually and collectively also plays a role in the incidence of forest and land fires in Indonesia (Purnomo et al, 2017;Irfan et al, 2020).…”
Section: Forest Fire In Indonesia and Peat Smoldering Phenomenamentioning
confidence: 99%
“…A case study in the study of Tymstra et al (2020) explains that natural factors mainly cause forest fires in Canada. Meanwhile, it has been widely stated that forest fire in Indonesia is also influenced by human factors such as land clearing activities by burning (Purnomo et al, 2017;Irfan et al, 2020;Jefferson et al, 2020). Even though the main factors causing fires in the two countries are different, the paradigm of forest fire disaster mitigation based on scientific assessment of physical variables in the form of CFFDRS in Canada can be followed to develop mitigation of forest fires in Indonesia.…”
Section: Forest Fire In Indonesia and Peat Smoldering Phenomenamentioning
confidence: 99%
“…The concept of sustainability goes beyond the passive persistence of social systems� In this context, sustainability does not refer to ecology and the environment, but rather to the ability of a social system to adapt to its physical, social, economic, and intellectual environment� This perspective on sustainability is consistent with the work of Barnard and Van der Merwe (2016), and Fien, Maclean and Park (2009), who focus on the capacity of social systems to adapt to a changing environment� Moreover, sustainability is not a single element, but a complex new paradigm that affects all areas and activities of social systems (Berzosa, Bernaldo & Fernández -Sanchez 2017)� Furthermore, it is a situational matter and depends on the indigenous contingencies and requirements of social systems� With this consideration, it is necessary to achieve a comprehensive and complete knowledge of the multidimensional concept of sustainability and its different aspects, as well as the development of indigenous humanities in this regard� Accordingly, the study of sustainability from the perspective of the Qur'an, especially for social systems in Muslim societies, is proposed� Muslims believe that this comprehensive holy book covers every aspect of human conduct and behaviour� The word sustainability is not found in its common meaning in the Qur'an, although by accepting the guiding authority of the Qur'an for all human beings, especially the Islamic society, the key themes of sustainability can be extracted from it� So far, numerous studies have been conducted on the sustainability of various organizations and institutions, especially universities, but there are comparatively few research studies on sustainability based on the Qur'an� For a better understanding, the authors of this paper classified the results of the existing studies into three categories based on their commonalities� First, some studies have attempted to explain and clarify the meaning and concept of sustainability from an Islamic perspective (Barry 2015;Sarkawi, Abdullah & Dali 2016)� Of course, most scholars have used the definition presented at the United Nations Conference in Stockholm (1972) to examine the concept of sustainability from the perspective of Islam and the Qur'an� In these studies, very few attempts have been made to achieve a deep understanding of sustainability and develop its conceptual and operational aspects based on Qur'anic teachings (Cincera et� al� 2018)� Other researchers have paid special attention to the principles and basic elements of sustainability (Matali 2012;Abdullah & Harun 2018)� However, due to the complexity of the concept of sustainability and, on the other hand, the comprehensiveness of the Qur'an, the principles and elements discussed have been considered to a very limited extent� Finally, most researchers have analysed and explained sustainability with an Islamic approach from the perspective of one of the dimensions of sustainability in particular, among which more attention has been paid to the environmental and economic dimensions (Jusoff, Samah & Akmar 2011;Vincenti 2017;Irfan et al� 2020;Ghoniyah & Amilahaq 2020;…”
Section: Introductionmentioning
confidence: 99%